PERLINDUNGAN HKI PRODUK SENTRA IKM KOTA SURAKARTA - Sutiyo; Dora kusumastuti (Adi Widya : Jurnal Pengabdian Masyarakat, 2022)
The still low protection of IPR for SMES products needs to be strengthened to protect the ownership rights of inventors on the recognition of other parties. The Harmoni Semanggi SMES Center of Surakarta City is one of the centers made by design by the Surakarta City Government. The SMES is a derivative of the batik SMES which is a superior product of the City of Surakarta and has export potential. However, the resulting product does not yet have IPR protection, so it is necessary to carry out community service activities in the form of socialization and counseling and assistance in obtaining IPR. Activities carried out by conducting outreach and assistance to the Semanggi SMES center actors. The result is an increase in partner knowledge about the urgency of IPR protection.